Development of Quantum Cryptography Algorithm for Data Security in Digital Communication System - Prabukusuma, M. Azhar (Marqcha Institute, 2023)
Data security in digital communication systems is becoming increasingly important given the threat of increasingly sophisticated cyber-attacks. The use of classical cryptography commonly used today faces significant challenges from the emergence of quantum computing. This research aims to develop and test a quantum cryptography algorithm specifically designed to enhance data security in digital communication systems. The research approach involves quantum key generation, quantum encryption using quantum principles such as superposition and entanglement, and testing the algorithm's robustness against quantum and other attacks. The application of the quantum cryptography algorithm in the Secure Messaging application case study resulted in a high level of security and efficiency in the use of computing resources. Robustness testing also showed that the algorithm is able to withstand various types of attacks, including sophisticated quantum attacks. The results of this research have far-reaching implications in improving the privacy and security of user data in digital communications. The next step is to develop and implement this algorithm on a wider scale, as well as evaluate the performance and efficiency of the algorithm for practical use in various contexts.